EVALUASI KINERJA KEUANGAN RUMAH SAKIT UMUMDAERAH âULINâ BANJARMASIN (PERBANDINGAN SEBELUMdan SESUDAHMENJADI BADAN LAYANAN UMUMDAERAH) - , Ratih Utami Hidayanti, Irfan Nursasmito, Drs., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is a case study in regional public hospital of Ulin Banjarmasin with title âThe Work Evaluation of Finance of Regional Public Hospital Ulin Banjarmasin (The Comparison Before and After to be The Institution of Regional Public Service). The purpose of this research was to compare and evaluate the work of finance Ulin Banjarmasin hospitals before and after becoming BLUD. This research will be conduct a hypotheses test to test the truth of earlier allegation. Techniques in data analysis using several financial ratios that are used as the indicators of the healt assessment of the work finance. From the calculation of all ratios will then be carried out statistical test, the test was used is Mann Whitney test and Wilcoxon test. The test was used to test significant differences between the work finance of Ulin Banjarmasin hospital before becoming BLUD and after becoming BLUD. Based on the weighting of the ratio calculated for the period before or after becoming BLUD, the grade of financial performance is in the same grade. There is in grade AA and there is in grade A. This suggests that the changes of status to BLUD not to be able for hospital to quickly improve the health of the work finance. Statistical test of overall the work finance showed the value of Exact Sig. [2*(1-tailed Sig.) by using Mann Whitney test and the value of Asymp. Sig. (2- tailed) by using Wilcoxon test is greater than 5% (0.05), so that Ha is rejected. That means there is not significant difference between the work finance before and after become BLUD. Statistical tests did show that there is no difference between before and after becoming BLUD, but if viewed one by one ratio calculated, results showing that fluctuate each year. There is ratio that is increasing and there is also decreased. The smooth of fun in implementing of IRPS before, of course, it also improves the financial working spirit wholly. This cannot also be separated with how the managementâs working spirit in managing the hospital financial. Therefore easiness use of funds should be fully utilized to improve the quality of service. Hospital management must also continue to improve their performance in terms of financial management. The pattern of financial management that have been defined must be obeyed and executed well. Financial management more efficient, effective, transparent and accountable to be improved so as to improve the quality of health level financial working.